Effect of Health Education in Improving Knowledge, Attitudes and Practices of Preventable Cancers amongst Reproductive Age Women A Randomized Field Trial - Rabbiya Sarwar, Hala Bashir Hashmi, Hina Mehmood, Fizza Anwar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The increasing burden of preventable cancers among women in low-middle income countries call for urgent development of constructive health strategies. The aim of this study was to determine the effect of health education on knowledge, attitude and practices of reproductive age women about preventable cancers in two peri-urban communities of Lahore. Material and Methods: The study was a Randomized field trial and the data was collected from women of reproductive age from areas of Lahore Shadewal (SC) and Satokatla (SI). SC stands for control group and SI for interventional group. Number of participants was 235 in each group. A validated questionnaire was administered to evaluate knowledge, attitude and practices for prevention of reproductive cancers from both groups. Then during next visit to intervention group, a health education program in form of group discussion, role play and demonstration related to preventable cancers was arranged. After 2 weeks of previous visit, questionnaires were again filled. Same questionnaire was filled by the comparison group without giving any intervention. Results: Before intervention mean total score for knowledge was 4.24 ± 2.30 in SC group and 4.68 ± 2.99 in SI group. After educating, mean total score of SC group the score came out to be 5.91 ± 3.014 whereas in SI group it was improved to 20.57 ± 2.755. The mean change in total score of knowledge of SC group was 1.67 ± 2.62 and 15.89 ± 3.35 in SI group. The mean change was found to be highly significant in SI group when compared with SC group, (p<0.001). The attitude and self-practice was also improved in SI group while females of SC showed no improvement, (p>0.05). Conclutions: The study highlighted the need for educational programs to create awareness regarding regular screening of gynecological preventable cancers.